2023
DOI: 10.1186/s42358-023-00306-2
|View full text |Cite
|
Sign up to set email alerts
|

Gut microbiota mediated the effects of high relative humidity on lupus in female MRL/lpr mice

Abstract: Introduction The relationship between humidity and systemic lupus erythematosus (SLE) has yielded inconsistent results in prior research, while the effects of humidity on lupus in animal experiments and its underlying mechanism remain inadequately explored. Methods The present study aimed to investigate the impact of high humidity (80 ± 5%) on lupus using female and male MRL/lpr mice, with a particular focus on elucidating the role of gut microbiot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…( R. torques spp. ) was found to be higher in the LN group than in the control group in one (1/14) clinical study [ 28 ] and two (2/5) animal studies [ 28 , 41 ], but one (1/7) animal study [ 44 ] found a lower abundance. The genus Lactobacillus and species Lactobacillus reuteri ( L. reuteri ) were mentioned as having changes in abundance in two (2/14) clinical studies [ 32 , 38 ] and three (3/7) animal studies [ 38 , 42 , 43 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…( R. torques spp. ) was found to be higher in the LN group than in the control group in one (1/14) clinical study [ 28 ] and two (2/5) animal studies [ 28 , 41 ], but one (1/7) animal study [ 44 ] found a lower abundance. The genus Lactobacillus and species Lactobacillus reuteri ( L. reuteri ) were mentioned as having changes in abundance in two (2/14) clinical studies [ 32 , 38 ] and three (3/7) animal studies [ 38 , 42 , 43 ].…”
Section: Resultsmentioning
confidence: 99%
“…Two (2/14) clinical studies [ 25 , 34 ] and five (5/7) animal studies [ 38 , 40 , 41 , 43 , 44 ] reported changes in inflammatory markers and intestinal barrier dysfunction markers. In both clinical and animal studies [ 25 , 36 , 44 ], the inflammatory indicator interleukin (IL)-6 was found to be increased in patients with LN but decreased after Lactobacillus treatment [ 40 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations